Variations in ambient and elevated temperature mechanical behavior of IN718 manufactured by selective laser melting via process parameter control - McLouth, Tait D.; Witkin, David B.; Bean, Glenn E.; Sitzman, Scott D.; Adams, Paul M.; Lohser, Julian R.; Yang, Jenn-Ming; Zaldivar, Rafael J. (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2020)
The present study considers the effects of process parameters on the microstructural development and mechanical properties of SLM Inconel 718. A continuous scanning strategy was used in conjunction with changes in laser spot size to emphasize texture development in the samples; it was found that aligned laser scan vectors (continuous scans) enhanced the crystallographic and morphological texture that forms during solidification when compared to multi-directional scan vectors (island scans). Although room temperature tensile testing did not exhibit variation in material properties, creep rupture testing showed a significant difference in ductility and time to failure. As texture and preferred crystallographic orientation were increased parallel to the loading direction, an increase of 51% in creep elongation was observed for the continuous scanning strategy. This behavior is linked to differences in damage accumulation mechanisms in the microstructure based on grain boundary orientation and precipitation. Furthermore, comparison of the mechanical behavior of SLM and wrought materials showed that wrought had ~10% greater tensile yield strength at room temperature, while in creep rupture the increase in elongation was as high as 640%. The primary difference between SLM and wrought material contributing to this discrepancy was the difference in NbC distribution. Although small differences in mechanical behavior can be induced in SLM material through process parameter variation, the separation in properties when compared to a wrought product are more significant. •Laser focal shift and scanning strategy can enhance microstructural texture.•Microstructural texture persists through HIP and heat treatment.•SLM IN718 is shown to be environmentally sensitive due to NbC precipitation.•Wrought material displays superior high temperature ductility when compared to SLM.